2024
DOI: 10.1002/adma.202402445
|View full text |Cite
|
Sign up to set email alerts
|

Revolutionizing Neurocare: Biomimetic Nanodelivery Via Cell Membranes

Jun Liao,
Lidong Gong,
Qingqiang Xu
et al.

Abstract: Brain disorders represent a significant challenge in medical science due to the formidable blood‐brain barrier (BBB), which severely limits the penetration of conventional therapeutics, hindering effective treatment strategies. This review delves into the innovative realm of biomimetic nanodelivery systems, including stem cell‐derived nanoghosts, tumor cell membrane‐coated nanoparticles, and erythrocyte membrane‐based carriers, highlighting their potential to circumvent the BBB's restrictions. By mimicking nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 276 publications
0
3
0
Order By: Relevance
“…38,39 The RBCbased drug delivery system has a long circulation time, excellent biocompatibility, and translational application prospects. 32,34,40,41 Based on the fact that P. gingivalis has a tendency to adhere to erythrocytes and acquire heme to sustain its growth and virulence (Figure 2D), a liposome containing an RBCs membrane was constructed to target P. gingivalis and deliver gallium porphyrin. Since P. gingivalis cannot distinguish between iron ions and gallium ions (Figure 2E), gallium porphyrins could be absorbed instead of iron porphyrins, thereby affecting the metabolism of P. gingivalis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 The RBCbased drug delivery system has a long circulation time, excellent biocompatibility, and translational application prospects. 32,34,40,41 Based on the fact that P. gingivalis has a tendency to adhere to erythrocytes and acquire heme to sustain its growth and virulence (Figure 2D), a liposome containing an RBCs membrane was constructed to target P. gingivalis and deliver gallium porphyrin. Since P. gingivalis cannot distinguish between iron ions and gallium ions (Figure 2E), gallium porphyrins could be absorbed instead of iron porphyrins, thereby affecting the metabolism of P. gingivalis.…”
Section: Resultsmentioning
confidence: 99%
“…At present, many studies have shown the advantages of cell membrane-associated nanomaterials in drug delivery. , The RBC-based drug delivery system has a long circulation time, excellent biocompatibility, and translational application prospects. ,,, Based on the fact that P. gingivalis has a tendency to adhere to erythrocytes and acquire heme to sustain its growth and virulence (Figure D), a liposome containing an RBCs membrane was constructed to target P.…”
Section: Resultsmentioning
confidence: 99%
“…The utilization of naturally occurring nanoparticles within biological systems has been employed to create novel structures that enhance the development of delivery systems through the utilization of inherent targeting capabilities. 162 Biomimetic systems have demonstrated considerable utility in the field of biomedicine, namely in applications like as drug delivery, gene transport, theranostics, and biosensing. This is mostly due to their exceptional biocompatibility, little toxicity, and notable interactive properties.…”
Section: Biomimetic Nanoparticlesmentioning
confidence: 99%